ANALISIS KELAYAKAN INDUSTRI RUMAH TANGGA GULA MERAH DI DESA GEMALASARI KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Zaini, Amrudin; Jahrizal, Jazrizal; Eka, Pailis Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to see the feasibility of the brown sugar household industry in the village of gemalasari, Rangsang District, Kepualuan Meranti Regency. The population and sample in this study were brown sugar home industries in Gemalasari Village which stated 10 businesses. The data used in this study are primary data and secondary data. Technique data through observation methods, and questionnaires. The data analysis method used is quantitative and descriptive analysis. Financial analysis is performed to analyze financial aspects such as Net Present Value (NPV), Benefeit Cost Ratio (B / C Ratio), Internal Rate Of Return (IRR), Payback Period (PP). And descriptive analysis to analyze nonfinancial feasibility such as market aspects, technical aspects, and socioeconomic aspects. The results of this study indicate that the brown sugar home industry in Gemalasari Village, Rangsang Subdistrict, Meranti Islands Regency is feasible to be developed. This can be seen from the results of the financial feasibility analysis which shows the NPV value of 28,826,971.1> 0, B / C Ratio 1.06> 1, IRR 32.5%> 12% and the payback period (PP) 2 years 1 month 28 days. So it can be denied that the brown sugar household industry in Gemalasari Village, Rangsang District, Meranti Islands Regency is feasible to develop financially in the research area.Keywords: small industry chop, brown sugar, Financial and non financial feasibility analysis, NPV, B / C Ratio, IRR, PP